Comparativa de propiedades ópticas de carillas feldespáticas vs carillas de disilicato de litio estratificado” revisión sistemática - Castillo Galarza, Cristian Sebastián (2025)
Dental veneers are a cosmetic treatment option that can reshape broken teeth, close cracks and restore vertical dimensions. Porcelain and lithium disilicate feldspar dental veneers have become significant materials used in dental restorations due to their biocompatibility, excellent aesthetic properties, adequate mechanical strength and high ease of use. Objective: To compare the optical properties of layered lithium disilicate and feldspathic lithium disilicate veneers by means of a literature review in order to provide knowledge on which material provides better aesthetic results. Method: A qualitative approach was used to analyze information from indexed journals publishing in the top quartile, using the PRISMA method. Information was retrieved from repositories such as Pubmed, Wiley and ScienceDirect over the last 5 years, using advanced search strings. Results: Initially a total of 122 scientific articles were obtained, but after a process of discarding and selection where inclusion and exclusion criteria were applied, only 8 articles were selected as valid for the research. Conclusions: It is concluded that when comparing the optical properties that stratified lithium disilicate and feldspathic veneers have, it was determined that feldspathic ones present better results such as a more homogeneous color and less translucent with better color variation values.